IIUM Ibadah disability scale (IIDS): design and conceptual framework - Sharifudin, Mohd Ariff; Wan Husin, Wan Rumaizi; Taib, Mai Nurul Ashikin (Zes Rokman Resources, 2016)
Illness does not alleviate the obligation of Muslim patients to perform religious duties such as prayer. The need for a systematic evaluation of patients’ ability to perform such duties needs to be highlighted and anticipated. Thus, a research was designed to develop a standard, objective evaluation scoring system to recognize disability levels of Muslim trauma patients in performing religious physical cleansing and prayer during their illness and improve the deliverance of assistance they need. This research involves five stages. 1-Identifying common and specific problems faced by trauma patients, 2-Constructing a disability score based on data obtained, 3-Incorporating Islamic rulings and pilot testing, 4-Validation and reliability testing, and 5-Patient categorization and development of an in-patient coding system. Trauma patients of general orthopaedic wards of a local institution were recruited for this research. In the initial phase of this research, we had identified problems contributing towards patients’ ability to perform religious practices during hospital admission. These can be grouped into four main factors; the patient, the staff delivering the assistance, hospital policies and availability of facilities. Subsequent phases of this research will focus more on the first and second factors. Three major outcomes are expected at the end of this research. A disability score to categorize trauma patients according to their needs, a manual based on Islamic rulings and convenience related to common and specific disabilities, and a coding system to assist physicians and hospital staff in scrutinizing the types of assistance required by patients. This will be the first scoring system that is constructed based on both patients’ and physicians’ perspectives of difficulties in performing religious duties. It will provide a balance approach in trauma patients’ care and deliverance of assistance wherever required. The proposed scoring system has potential of becoming a standard of practice in a more holistic patient care in accordance to the much-anticipated ibadah-friendly hospital.